EFEKTIVITAS METODE REPETITION DAN KELANCARAN MEMBACA AL-QUR'AN DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL AL-QUR'AN SISWA KELAS IV SD NEGERI 1 FAKFAK - Rudin, Suratna Dewi; Amin, Surahman; Sudirman (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2024)
This research aims to analyze the effectiveness of the repetition method and fluency in reading the Al-Qur'an towards increasing the ability to memorize the Al-Qur'an in class IV students at SDN 1 Fakfak. The type of research is quantitative experimental research. Data sources are students and supporting documents. The methods of data collection used are observation, questionnaires, tests, and documentation. The data analysis used is descriptive and paired data analysis. Based on the analysis, in the experimental class, the t-value was -22.784 smaller than -2,08. In the control class, the t-value was -8.717 smaller than -2,064. So the first hypothesis and second hypothesis are accepted. Likewise, the f-value obtained is 1197.811 smaller than 2,09 so the third hypothesis is accepted. Based on the results, it can be concluded that there are differences between the pre-test and post-test in both the experimental and the control classes. Therefore, the repetition method has an effect on increasing students' memorization, as well and the reading fluency method has an effect on improving students' memorization simultaneously the repetition method and reading fluency of the Al-Quran have an effective effect in increasing the memorization of Class IV students at SDN 1 Fakfak